BUILDING COMMUNITY RESILIENCE THROUGH EDUCATIONAL ACTIVITIES FOR WOMEN IN COUNTERING RADICALISM AND TERRORISM - Andina Mustika Ayu; Efan Setiadi; Catherin Lumban Tobing (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
This study attempts to describe educational activities for women that have a positive contribution as a strategy to prevent the spread of radicalism and terrorism. Efforts to combat terrorism in Indonesia to date still leave much to be desired. Government programs such as deradicalization and disengagement have not shown satisfactory results and cannot be considered effective measures to prevent radicalism. Based on the brief description of the background above, this study aims to describe how women's education programs can be used as a measure to prevent radicalism and terrorism and to describe why women's education activities can make a positive contribution to increasing community resilience to the spread of radicalism. The method used in this study is a qualitative method with a case study approach. Through women's education activities, the researcher attempts to see how mothers and women play a very important role in the family in educating and preventing the development of radicalism.